Building The Independence of PKK Mothers During the Covid-19 Pandemic Through Training in Kokedama Making on Sukarami Subdistrict, Palembang - Astriani, Meli; Saputri, Wulandari; Aseptianova, Aseptianova; Hidayat, Saleh; Antika, Rindi Novitri; Wijayanti, Tutik Fitri (Altifani Journal: International Journal of Community Engagement, 2021)
During the Covid-19 period, it was considered quite disruptive to the economy of every family. One promising entrepreneurial opportunity during this pandemic is the use of waste to become valuable goods. Kokedama is a gardening technique from Japan that can reduce plastic pots, an alternative to indoor plants with aesthetic value and high selling value. This service aims to provide training in making kokedama to Sukarami District Family Welfare Advisors (PKK). The community service method uses a training method consisting of three stages: the delivery of material, demonstrations, and practice of making kokedama, and evaluation of training activities. The results of this service, the community response to the material, stated that 100% of training participants did not know kokedama, 60% of participants were satisfied with the kokedama training, and 50% of participants noted that the time used was quite efficient for training and practice. In the future, the acquired skills are expected to provide provisions for improving family welfare through innovating ornamental plants by utilizing coco fiber waste to become kokedama.